Assessing the staffing needs for primary health care centers in Cross River State, Nigeria: a workload indicators of staffing needs study - S. C. Okoroafor; A. Ahmat; M. Osubor; J. Nyoni; J. Bassey; W. Alemu (BMC, 2022)
Abstract Background A major human resources for health challenge for Nigeria is ensuring the availability and retention of adequate competent health workers in the right mix to provide health care particularly at primary health care facilities in remote and rural communities. This study applied the Workload Indicators of Staffing Need (WISN) method to determine the numbers of nurses, midwives, community health officers (CHOs), community health extension workers (CHEWs), and junior community health extension workers (JCHEWs) required to cope with health care service delivery at primary health care facilities in Cross River State; compare workloads of different cadres at selected health facilities, and identify facilities with highest workload pressure. Methods Cross River State in Nigeria has 18 local governments, 196 wards, and an estimated population of over three million people. We used the WISN method to estimate the numbers of nurses/midwives, CHOs/CHEWs, and JCHEWs required to cope with the workload in the 196 ward-level primary health care facilities. Findings Basic services provided by nurses/midwives, and CHOs/CHEWs were typical of the primary health care level. They are antenatal care, routine immunization, child welfare clinic, family planning, treatment of minor ailments, assisted and normal deliveries, postnatal care, emergencies, care of tuberculosis patients, and referrals. Findings show that available nurses/midwives for the 196 PHC facilities were 79, and the calculated requirement was 209, WISN ratio of 0.4 and difference of − 130; the existing number of CHOs/CHEWs was 808, the calculated requirement was 1,258, WISN ratio of 0.6, with a difference of − 450; and the number of existing JCHEWs was 258, the calculated requirement was 203, WISN ratio of 1.3 with a difference of 55. Cross River State had only 40% of required nurses and midwives; and 60% of CHOs/ CHEWs needed to provide health services in the ward-level PHC facilities. Conclusion The findings from this study indicated marked shortages of needed health workforce particularly nurses and midwives at the primary level of care; and overlap in some of the tasks performed by nurses/midwives, CHO/CHEWs, and JCHEWs.